Neutrophil-to-lymphocyte ratio as a novel predictor of sarcopenia in maintenance hemodialysis patients: a cross-sectional study exploring associations across body composition categories - Yogesh M.; Parth Anilbhai Parmar; Soumya Sharma; Jay Pareshbhai Kakadiya; Dhruv Lakkad (BMC Musculoskeletal Disorders)
Abstract Background Sarcopenia is prevalent among hemodialysis patients and is associated with poor outcomes. The neutrophil-to-lymphocyte ratio (NLR), an easily obtainable marker of inflammation, may predict sarcopenia risk. This study aimed to investigate the association between NLR and sarcopenia risk in maintenance hemodialysis patients, examining this association in the context of obesity. Methods This cross-sectional study included 411 maintenance hemodialysis patients. Sarcopenia was diagnosed using the Asian Working Group for Sarcopenia criteria-2019 (AWGS 2019). Body composition was assessed using bioelectrical impedance analysis. Logistic regression models examined associations between NLR and sarcopenia risk, adjusting for potential confounders. Analyses were stratified by obesity status. Results The prevalence of sarcopenia was 51% (95% CI: 45.1-54.9%), with 37.2% classified as sarcopenic non-obese and 13.6% as sarcopenic obese. In fully adjusted models, each unit increase in NLR was associated with 10% higher odds of sarcopenia overall (OR 1.10, 95% CI: 1.00-1.21, p = 0.048). This association remained significant in sarcopenic obese patients (OR 1.15, 95% CI: 1.00-1.32, p = 0.049). Patients in the highest NLR tertile had 1.95 times higher odds of sarcopenia compared to the lowest tertile (95% CI: 1.12–3.40, p = 0.018), with a significant trend across tertiles (p-trend = 0.015). Conclusions NLR is independently associated with sarcopenia risk in hemodialysis patients, including those with obesity. These findings suggest NLR could serve as a simple, cost-effective tool for identifying hemodialysis patients at high risk of sarcopenia, potentially facilitating early intervention strategies.